Rani Lakshmi Bai and Major General Hugh Rose: A comparative analysis - Thakur, R.S. and Kapoor, Nikhil (U.S.I. Journal)
The Indian Revolt of 1857 was led by many capable leaders from the revolvers$1 (Bside, namely, Rani Lakshmi Bai, Nana Saheb, Kunwar Singh, and Begum Hazrat Mahal, whereas the fight by the British East India Company forces was steered by senior officers such as Major General J Outram, Major General Hugh Massey Wheeler, Major General Hugh Rose, Brigadier Henry Lawrence and Brigadier John Nicholson.1 The battles of 1857 have been described by numerous authors in great detail in the last century and a half; however, the comparative analysis of the leadership qualities and military skills of the two most prominent leaders of the revolt, Rani Lakshmi Bai and her principal opponent, Major General Hugh Rose, does not find a mention in history. This article, which is a product of the research of rare/vintage books available in the libraries of Army War College and the Infantry School Mhow, besides other sources available on the subject, endeavors to bridge this historical gap. It is hoped that the article will provide a new perspective on the leadership aspect during an important event of Indian military history.- Reproduced s
Keywords: Indian Revolt of 1857, Rani Lakshmi Bai, British East India Company